PELATIHAN PENGASUHAN ANAK USIA DINI UNTUK CARETAKER DAYCARE DI KECAMATAN LIDAH WETAN - Ruqoyyah Fitri; Dewi Komalasari; Melia Dwi Widayanti (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2023)
Daycare is a form of Institution in Early Childhood Education. Many daycare, especially in Lidah Wetan Subdistrict, does not yet have competent caregivers for children because the last education of most caregivers is high school, not graduates from the Early Childhood Education Study Program or people who already have certification from a baby sitter institution. This impacts the education and care provided to daycare, which tends to be disoriented, so it is necessary to carry out a training process for daycare care takers to provide knowledge about how to care for early childhood. Training for daycare caretakers is given to daycare caretakers in Lidah Wetan District. The methods implemented are discussion, lecture, simulation, evaluation. Data collection techniques to measure the pretest and posttest using a questionnaire via google form. The data analysis technique used the N-GAIN SCORE. The result of calculating the average difference between the posttest and pretest scores is 0.71, indicating a high category. The results of the calculation of the percentage n-gain score obtained an average value of 71.49, so it can be concluded that childcare training is proven to be effective in improving parenting skills for daycare caretakers in Lidah Wetan District, Surabaya. Keywords: caretaker, daycare, child care